Surface structure modified biological ceramic bone repair scaffold and preparation method thereof

By modifying the multi-layer powder coating on the surface of the bioceramic bone repair scaffold, the problem of insufficient hydrophilicity and surfactivity caused by the surface density of the bioceramic scaffold is solved, which significantly improves the hydrophilicity and surfactivity of the scaffold and promotes the bone repair process.

CN119950815AActive Publication Date: 2025-05-09YANTAI ZHENGHAI BIO TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510321429.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-05-09
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

The ceramic surface structure of the bioceramic bone repair scaffold is dense, with low surface roughness and surface energy, resulting in low surface activity and poor hydrophilicity of the material, affecting the bone repair effect.

Method used

Through the surface structure modification method, the surface of the bioceramic bracket is modified using a multi-layer powder coating. The powder particle sizes of the first and second layers of impregnation liquids are 20-30 μm and 5-8 μm, respectively, to increase the surface roughness and surface energy of the material.

Benefits of technology

It significantly improves the hydrophilicity and surfactivity of the bioceramic scaffold, promotes blood infiltration, blood clot formation, cell adhesion and growth, active factor release and blood vessel growth, thereby accelerating the bone repair process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119950815A_ABST
    Figure CN119950815A_ABST
Patent Text Reader

Abstract

The invention discloses a surface structure modified biological ceramic bone repair scaffold and a preparation method thereof, and the preparation method comprises the following steps: step S1, carrying out ball milling, printing, glue discharging and sintering on a mixture containing ceramic powder, photosensitive resin and a dispersant to obtain a porous structure three-dimensional scaffold; s2, dipping the porous structure three-dimensional scaffold in the dipping liquid to obtain a surface structure modified biological ceramic bone repair scaffold, the impregnation liquid comprises a first layer of impregnation liquid and a second layer of impregnation liquid. The biological ceramic scaffold provided by the invention has super hydrophilicity, high surface activity and high fusion speed with bone tissues, is beneficial to osteogenesis and vascularization, and is a bone repair material with good biological activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a bioceramic bone repair scaffold with modified surface structure and a preparation method thereof, belonging to the technical field of bioceramic bone repair scaffolds. Background Art

[0002] At present, it has become very common to treat bone defects by implanting artificial bones in clinic. The ideal bone repair scaffold needs to have good biocompatibility, biodegradability, three-dimensional porous structure, stable mechanical strength, good hydrophilicity, high surface activity, etc.

[0003] Bioceramic scaffolds are widely used in bone tissue engineering due to their chemical composition and material properties that are conducive to osteogenesis. Compared with traditional pore-forming agent molding processes, bioceramics prepared by 3D printing technology have the natural advantages of highly controllable pore size and structure, and the mechanical strength of bioceramic scaffolds is stable.

[0004] The common problems of bioceramic scaffolds are: the ceramic surface structure is dense, the surface roughness and surface energy are low, resulting in low surface activity and poor hydrophilicity of the material. Ceramic scaffolds with high surface activity and hydrophilicity are more conducive to blood infiltration after implantation, can stabilize blood clots, and are more conducive to osteogenesis; at the same time, scaffold materials with high active surfaces can quickly release and exchange ions after implantation, which is conducive to the loading of active factors, cell adhesion and growth, extracellular matrix deposition and blood vessel growth, thereby promoting early osteogenesis. Therefore, the development of a porous bioceramic scaffold with high surface activity and hydrophilicity is of great value in the field of bone repair. Summary of the invention

[0005] To solve the above problems, the present invention provides a method for preparing a surface structure modified bioceramic bone repair scaffold. The bioceramic bone repair scaffold prepared by surface structure modification has ultra-high hydrophilicity and surface activity, and the preparation method is simple and easy to operate.

[0006] According to one aspect of the present invention, a method for preparing a bioceramic bone repair scaffold with modified surface structure is provided, the preparation method comprising the following steps: Step S1: ball milling, printing, debinding, and sintering a mixture containing ceramic powder, photosensitive resin, and dispersant 1 to obtain a porous three-dimensional scaffold; Step S2: immersing the porous three-dimensional scaffold in an immersion solution to obtain a bioceramic bone repair scaffold with modified surface structure; The impregnation liquid comprises a first layer of impregnation liquid and a second layer of impregnation liquid; In the first layer of impregnation liquid, the powder particle size D50 = 20 ± 3 μm, D90 = 30 ± 5 μm; In the second layer of impregnation liquid, the powder particle size D50 = 5 ± 2 μm, D90 = 8 ± 2 μm.

[0007] Optionally, the impregnation liquid includes water, powder and dopamine.

[0008] Optionally, the powder is selected from at least one of bioactive glass, β-tricalcium phosphate, α-tricalcium phosphate, white wellstone, hydroxyapatite, calcium silicate, magnesia chalcedony, and diopside.

[0009] Optionally, the concentration of dopamine in the impregnation solution is 2-8 g / L.

[0010] Optionally, in the impregnation solution, the concentration of dopamine is independently selected from any value among 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L or a range between any two of the above values.

[0011] Optionally, in the first layer of impregnation solution, the mass proportion of powder in the solution is 15% to 25%.

[0012] Optionally, in the first layer of impregnation solution, the mass proportion of powder in the solution is independently selected from any value of 15%, 18%, 20%, 22%, 25% or a range between any two of the above.

[0013] Optionally, in the second layer of impregnation solution, the powder mass proportion in the solution is 8-15%.

[0014] Optionally, in the second layer of impregnation solution, the mass proportion of powder in the solution is independently selected from any value of 8%, 9%, 10%, 12%, 15% or a range between any two of the above.

[0015] Optionally, the preparation method of the impregnation liquid comprises: mixing water and dopamine, stirring for 10 minutes to 2 hours, adding powder and mechanically stirring for 6 to 24 hours to obtain the impregnation liquid.

[0016] Optionally, after the water and dopamine are mixed, the pH value is adjusted to 7.5-9.0.

[0017] Optionally, in step S2, the porous three-dimensional scaffold is immersed in a first layer of impregnation liquid 1, dried 1, immersed in a second layer of impregnation liquid 2, dried 2, and sintered 2 to obtain a bioceramic bone repair scaffold with modified surface structure.

[0018] Optionally, in step S2, the sintering temperature 2 is 800-1000° C., and the sintering time 2 is 30-180 min.

[0019] Optionally, in step S2, the sintering temperature 2 is independently selected from any value of 800°C, 850°C, 900°C, 950°C, 1000°C or a range between any two of the above values.

[0020] Optionally, in step S2, the sintering time 2 is independently selected from any value among 30 min, 60 min, 90 min, 120 min, 150 min, 180 min or a range between any two of the above values.

[0021] Optionally, the time of the immersion 1 and the immersion 2 is independently selected from 5 to 30 minutes.

[0022] Optionally, the temperatures of drying 1 and drying 2 are independently selected from 40 to 90° C., and the times of drying 1 and drying 2 are independently selected from 1 to 5 hours.

[0023] Optionally, in step S1, the ceramic powder is selected from at least one of β-tricalcium phosphate, α-tricalcium phosphate, white wellstone, hydroxyapatite, calcium silicate, magnesia chalcedony, and diopside.

[0024] Optionally, the photosensitive resin is selected from at least one of commercial photosensitive resin Ausbond A370 or Formlabs photosensitive resin.

[0025] Optionally, the dispersant is selected from at least one of propylene glycol methyl ether, BYK-111, Triton X-100, KH-550, and KH-560.

[0026] Optionally, the mass ratio of the ceramic powder, the photosensitive resin and the dispersant is 1 g: (0.3-0.5) g: (0.05-0.1) g.

[0027] Optionally, the ball milling time is 28 to 56 hours.

[0028] Optionally, the printing method is three-dimensional printing technology, and the molding accuracy of the three-dimensional printing technology is 30-100 μm, wherein the pore size distribution of the bracket is 50-800 μm, accounting for more than 85%.

[0029] Optionally, in step S1, the debinding temperature is 400-700° C., and the debinding time is 180-300 min.

[0030] Optionally, in step S1, the temperature of sintering 1 is 1150-1450° C., and the time of sintering 1 is 120-500 min.

[0031] According to another aspect of the present application, a surface structure-modified bioceramic bone repair scaffold prepared by the above-mentioned preparation method is provided.

[0032] As an optional implementation mode, the present invention is implemented by the following technical solution: The preparation method of the surface structure modified bioceramic bone repair scaffold comprises the following steps: (1) Preparation of porous bioceramic scaffolds: ceramic powder and photosensitive resin dispersant are mixed evenly, formed by 3D printing technology, and sintered to obtain a 3D scaffold with a porous structure; (2) Surface modification: Two layers of powder coating are applied on the surface of the porous three-dimensional scaffold by solution impregnation method, and then sintered to obtain a bioceramic scaffold with modified surface structure.

[0033] In step (2), the impregnation process is to prepare a first layer and a second layer of impregnation solution respectively, first immerse the three-dimensional scaffold in the first layer of impregnation solution, ultrasonically disperse for 5-30 minutes, shake off the excess solution, dry or bake, place it in the second layer of impregnation solution, ultrasonically disperse for 5-30 minutes, shake off the excess solution, dry or bake, and obtain a bioceramic scaffold with modified surface structure after sintering.

[0034] The beneficial effects that the present invention can produce include: 1) The porous bioceramic scaffold provided by the present invention is obtained by a three-dimensional printing process, and can prepare components with complex and precise structures, high porosity and good pore connectivity.

[0035] 2) The surface structure modified bioceramic bone repair scaffold provided by the present invention is structurally modified on the surface of the porous three-dimensional scaffold by a solution impregnation method. Compared with the traditional bioceramic scaffold with a dense surface structure, the present invention uses two layers of impregnation, the first layer is impregnated with large particles, and the second layer is impregnated with small particles, thereby increasing the surface roughness of the material and improving the surface energy of the material. By adjusting the sintering temperature after impregnation, the material has super hydrophilicity and surface activity, which is beneficial to stabilizing blood clots, promoting cell adhesion and growth, accelerating interfacial ion exchange, promoting extracellular matrix deposition and blood vessel growth, thereby promoting early osteogenesis. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The pore size range and distribution diagram of the three-dimensional printed porous scaffold of the present invention; Figure 2 This is a structural diagram of a three-dimensional printed porous scaffold of the present invention; Figure 3 The pore size range and distribution diagram of the three-dimensional printed porous scaffold with surface structure modification of the present invention; Figure 4 A diagram showing the structure of a three-dimensionally printed porous scaffold with modified surface structure according to the present invention; Figure 5The surface morphology of the three-dimensional printed porous scaffold of the present invention (a1) (magnified 500 times), (a2) (magnified 5000 times), (b1) (magnified 500 times), (b2) (magnified 5000 times); Figure 6 This is the cell proliferation rate data of the present invention. DETAILED DESCRIPTION

[0037] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0038] Unless otherwise specified, the raw materials and reagents in the examples of this application were purchased through commercial channels.

[0039] The experimental methods used in the following examples are all conventional methods unless otherwise specified. The quantitative tests in the following examples were repeated three times, and the results were averaged.

[0040] Example 1 Preparation of porous scaffolds of white calcium silicate bioceramics: (1) Weigh and mix 20 g of photosensitive resin Ausbond A370 and 3 g of dispersant propylene glycol methyl ether and place them in a ball mill filled with zirconium oxide grinding balls. Add 50 g of white asphalt powder into the ball mill and mix them for 40 h. Place the mixed slurry in the slurry tank of a DLP light-curing 3D printer and print it according to the pre-set pattern. The thickness of the molding layer is 50 μm. Wash it in anhydrous ethanol and remove the uncured slurry to obtain a bioceramic porous scaffold green body.

[0041] (2) The bioceramic porous scaffold green body was debinded at 500 ℃ for 3 h and sintered at 1300 ℃ for 3 h to finally obtain the white calcium silicate bioceramic porous scaffold.

[0042] Example 2 Surface structure modification of bioceramic porous scaffolds: (1) Preparation of the first layer of impregnation solution: Add 2 g dopamine into 500 mL purified water, add a small amount of Na2CO3 to adjust the solution pH to 8.5, stir mechanically for 2 h, add 90 g β-tricalcium phosphate powder, and continue stirring for 20 h. The particle size of the β-tricalcium phosphate powder is D50 = 19.8 μm, D90 = 31.1 μm.

[0043] (2) Preparation of the second layer of impregnation solution: Add 2 g of dopamine into 500 mL of purified water, add a small amount of Na2CO3 to adjust the solution pH to 8.5, stir mechanically for 2 h, add 50 g of bioactive glass powder, and continue stirring for 20 h. The particle size of the bioactive glass powder 45S5 is D50 = 4.5 μm, D90 = 8.6 μm.

[0044] (3) The 10 three-dimensional scaffolds obtained in Example 1 were first immersed in the first layer of impregnation solution, ultrasonically dispersed for 30 minutes, and the excess solution was shaken off. The scaffolds were dried in an electric blast drying oven at 60°C for 3 hours. The dried scaffolds were immersed in the second layer of impregnation solution, ultrasonically dispersed for 10 minutes, and the excess solution was shaken off. The scaffolds were dried in an electric blast drying oven at 60°C for 3 hours. The dried scaffolds were sintered at a high temperature of 950°C for 60 minutes to obtain a bioceramic porous scaffold with a modified surface structure.

[0045] Example 3 Preparation of porous scaffolds of white calcium silicate bioceramics: (1) Weigh and mix 20 g of photosensitive resin Ausbond A370 and 3 g of dispersant propylene glycol methyl ether and place them in a ball mill filled with zirconium oxide grinding balls. Add 50 g of β-tricalcium phosphate powder into the ball mill and mix them for 28 h. Place the mixed slurry in the slurry tank of a DLP light-curing 3D printer and print it according to the pre-set pattern. The thickness of the molding layer is 30 μm. Wash it in anhydrous ethanol and remove the uncured slurry to obtain a bioceramic porous scaffold green body.

[0046] (2) The bioceramic porous scaffold green body was debinded at 400 °C for 300 min and sintered at 1150 °C for 500 min to finally obtain the white calcium silicate bioceramic porous scaffold.

[0047] Example 4 Surface structure modification of bioceramic porous scaffolds: (1) Preparation of the first layer of impregnation solution: Add 2 g of dopamine into 500 mL of purified water, add a small amount of Na2CO3 to adjust the solution pH to 7.5, stir mechanically for 2 h, add 76 g of β-tricalcium phosphate powder, and continue stirring for 6 h. The particle size of the β-tricalcium phosphate powder is D50 = 17 μm, D90 = 25 μm.

[0048] (2) Preparation of the second layer of impregnation solution: Add 2 g of dopamine into 500 mL of purified water, add a small amount of Na2CO3 to adjust the pH of the solution to 7.5, stir mechanically for 2 h, add 41 g of white asphalt powder, and continue stirring for 6 h. The particle size of the white asphalt powder is D50 = 3 μm, D90 = 6 μm.

[0049] (3) The 10 three-dimensional scaffolds obtained in Example 3 were first immersed in the first layer of impregnation solution, ultrasonically dispersed for 5 minutes, and the excess solution was shaken off. The scaffolds were dried in an electric blast drying oven at 40°C for 5 hours. The dried scaffolds were immersed in the second layer of impregnation solution, ultrasonically dispersed for 5 minutes, and the excess solution was shaken off. The scaffolds were dried in an electric blast drying oven at 40°C for 5 hours. The dried scaffolds were sintered at a high temperature of 800°C for 180 minutes to obtain a bioceramic porous scaffold with a modified surface structure.

[0050] Example 5 Surface structure modification of bioceramic porous scaffolds: (1) Preparation of the first layer of impregnation solution: Add 2 g of dopamine into 500 mL of purified water, add a small amount of Na2CO3 to adjust the solution pH to 9.0, stir mechanically for 10 min, add 125 g of β-tricalcium phosphate powder, and continue stirring for 24 h. The particle size of the β-tricalcium phosphate powder is D50 = 23 μm, D90 = 35 μm.

[0051] (2) Preparation of the second layer of impregnation solution: Add 2 g of dopamine into 500 mL of purified water, add a small amount of Na2CO3 to adjust the solution pH to 9.0, stir mechanically for 10 min, add 75 g of white asphalt powder, and continue stirring for 24 h. The particle size of the white asphalt powder is D50 = 7 μm and D90 = 10 μm.

[0052] (3) The 10 three-dimensional scaffolds obtained in Example 3 were first immersed in the first layer of impregnation solution, ultrasonically dispersed for 30 minutes, and the excess solution was shaken off. The scaffolds were dried in an electric blast drying oven at 90°C for 1 hour. The dried scaffolds were immersed in the second layer of impregnation solution, ultrasonically dispersed for 30 minutes, and the excess solution was shaken off. The scaffolds were dried in an electric blast drying oven at 90°C for 1 hour. The dried scaffolds were sintered at a high temperature of 1000°C for 30 minutes to obtain a bioceramic porous scaffold with a modified surface structure.

[0053] Comparative Example 1 This example is a comparative example. The white asperite bioceramic porous scaffold obtained in Example 1 is placed in a first layer of impregnation solution for impregnation treatment to obtain a layer of bioceramic porous scaffold with modified surface structure.

[0054] The specific steps are as follows: the preparation of the first layer of impregnation solution and the particle size requirements of the powder are completely consistent with the operating procedures of step (1) in Example 2; the white asphalt bioceramic porous scaffold obtained in Example 1 is placed in the first layer of impregnation solution, ultrasonically dispersed for 10 minutes, the excess solution is shaken off, and the scaffold is dried in an electric blast drying oven at 60°C for 3 hours; the scaffold after drying is subjected to high-temperature sintering at a sintering temperature of 950°C and a heat preservation time of 60 minutes, thereby obtaining a bioceramic porous scaffold with a modified surface structure.

[0055] Comparative Example 2 This example is a comparative example, and the white calcium silicate bioceramic porous scaffold obtained in Example 1 is placed in two layers of impregnation solution for impregnation treatment, respectively, to obtain a two-layer surface structure modified bioceramic porous scaffold. Among them, the powder of the first layer of impregnation solution is bioactive glass 45S5, and the powder particle size is: D50 = 4.5 μm, D90 = 8.6 μm; the powder of the second layer of impregnation solution is β-tricalcium phosphate, and the powder particle size is: D50 = 19.8 μm, D90 = 31.1 μm, and the remaining steps are completely consistent with Example 2.

[0056] Comparative Example 3 The sintering temperature of 950° C. in step (3) of Example 2 was replaced by 750° C., and the remaining preparation steps remained the same as those in Example 2.

[0057] Comparative Example 4 The sintering temperature of 950° C. in step (3) of Example 2 was replaced by 1100° C., and the remaining preparation steps remained the same as those in Example 2.

[0058] Test Example 1 The performance test and results of the product of the present invention are as follows: (1) Total porosity and pore size distribution study: The bioceramic scaffolds obtained in Example 1 and Example 2 were subjected to micro-CT scanning, and the pore size distribution and structure of the porous scaffolds before and after surface structure modification are shown in the figure. Figures 1 to 4 As shown. Figure 1 As shown in the figure, before surface structure modification, the total porosity of the material is 60%, the pore size distribution of the material is 91% in the range of 50-800 μm, and 45% in the range of 50-600 μm; Figure 3As shown in the figure, after surface structure modification, the total porosity of the material is 50%, 50-800 μm accounts for 99%, and 50-600 μm accounts for 85%. The pore size distribution results show that after surface structure modification, the pore size of the scaffold material tends to decrease, indicating that the powder in the impregnation solution has successfully bound to the surface of the scaffold material, and the number of pores of each size after surface modification presents a normal distribution, which is close to the pore size range of natural bone tissue. The scaffold with this pore size range is conducive to the growth of bone tissue (see Figure 2 3D printed porous scaffolds and Figure 4 3D printed porous scaffolds with modified surface structures).

[0059] (2) Scanning electron microscopy study: The surface morphology of the bioceramic scaffolds obtained in Example 1 and Example 2 was observed under a scanning electron microscope. Figure 5 As shown, compared with the surface structure-modified 3D printed porous scaffolds (b1 and b2), the surface structure-modified 3D printed porous scaffolds (a1 and a2) of Example 1 have higher surface roughness. Therefore, the surface structure modification improves the surface energy of the ceramic scaffold, which is beneficial to the hydrophilicity and blood infiltration of the material, and is beneficial to the ion exchange at the interface, thereby promoting the ingrowth of bone tissue.

[0060] (3) Hydrophilicity study: The samples obtained from Examples 1, 2, 4 and 5 Comparative Examples 1 and 2 were evaluated for hydrophilicity, and the specific operation steps were as follows: Weigh the sample (recorded as m1) and place it in a beaker filled with purified water. Take it out and weigh it after 30 s, 1 min, and 2 min respectively (recorded as m2). Calculate the water absorption rate of the sample according to the following formula: Water absorption = (m2 - m1) / m1 × 100% The water absorption test results are shown in Table 1. Compared with Example 1 and Example 3 (without surface structure modification), the water absorption of the surface structure modified stents (Example 2, Example 4 and Example 5) is significantly improved. Comparative Example 1 is a stent with only one layer of larger particle size modified, and Comparative Example 2 is a stent with a smaller particle size modified first and then a larger particle size modified. Its hydrophilicity is improved to a certain extent compared with Example 1. Among them, the stents of Example 2, Example 4 and Example 5 are modified with 2 layers of powder coating, and the powder particle sizes of the 2 layers of powder are respectively controlled within the specified range of the powder. Its water absorption rate is the highest, and the water absorption is basically saturated within only 30 s. Therefore, the stent obtained by this powder particle size has the best hydrophilicity. The reasons are analyzed as follows: after high-temperature sintering, the surface structure of the ceramic stents without surface structure modification (Examples 1 and 3) is relatively dense, the surface roughness of the material is relatively low, the surface energy of the material is relatively low, and the hydrophilicity is relatively poor; after the powder is modified on the surface of the stent and sintered at a relatively low temperature, the surface of the stent is modified with a relatively rough and loose structure, the surface roughness of the material is increased, and thus the hydrophilicity is significantly improved. At the same time, the modified powder particle size is also particularly important. First modifying the large particle size (D50 = 20 ± 3 μm, D90 = 30 ± 5 μm) and then modifying the small particle size (D50 = 5 ± 2 μm, D90 = 8 ± 2 μm) makes the specific surface area of ​​the material larger, so the hydrophilicity of Example 2 is better; combined with Comparative Examples 3 and 4, when the sintering temperature after impregnation is not between 800 and 1000°C, when the sintering temperature is lower than 800°C, the modified powder is not firmly bonded to the surface of the bracket, the surface structure modification is not obvious, and the hydrophilicity is poor; when the sintering temperature is higher than 1000°C, the modified powder forms a relatively dense structure on the surface of the bracket, the surface roughness of the material is low, and the hydrophilicity is poor.

[0061] Table 1 Water absorption test results

[0062] (4) Cytotoxicity and cell proliferation rate studies: The samples obtained in Example 1 and Example 2 were subjected to cytotoxicity and cell proliferation rate research experiments: using human fibroblasts (MRC5) as a model, the cell proliferation rate was tested by MTT method after 48h and 72h of culture. The test results are as follows: Figure 6 The bioceramic porous scaffold with surface structure modification has good cell compatibility.

[0063] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a surface structure-modified bioceramic bone repair scaffold, characterized in that: The preparation method comprises the following steps: Step S1: ball milling, printing, debinding, and sintering a mixture containing ceramic powder, photosensitive resin, and dispersant 1 to obtain a porous three-dimensional scaffold; Step S2: immersing the porous three-dimensional scaffold in an immersion solution to obtain a bioceramic bone repair scaffold with modified surface structure; The impregnation liquid comprises a first layer of impregnation liquid and a second layer of impregnation liquid; In the first layer of impregnation liquid, the powder particle size D50 = 20 ± 3 μm, D90 = 30 ± 5 μm; In the second layer of impregnation liquid, the powder particle size D50 = 5 ± 2 μm, D90 = 8 ± 2 μm.

2. The preparation method according to claim 1, characterized in that: The impregnation liquid comprises water, powder and dopamine; Preferably, the powder is selected from at least one of bioactive glass, β-tricalcium phosphate, α-tricalcium phosphate, leontoposite, hydroxyapatite, calcium silicate, magnesia chalcedony, and diopside; Preferably, the concentration of dopamine in the impregnation solution is 2-8 g / L.

3. The preparation method according to claim 1, characterized in that: In the first layer of impregnation solution, the powder mass proportion in the solution is 15% to 25%; Preferably, in the second layer of impregnation solution, the mass proportion of powder in the solution is 8-15%.

4. The preparation method according to claim 1, characterized in that The preparation method of the impregnation liquid comprises: mixing water and dopamine, stirring for 10 minutes to 2 hours, adding powder and mechanically stirring for 6 to 24 hours to obtain the impregnation liquid; Preferably, after the water and dopamine are mixed, the pH value is adjusted to 7.5-9.

0.

5. The preparation method according to claim 1, characterized in that: In the step S2, the porous three-dimensional scaffold is immersed in a first layer of an impregnation liquid for 1, dried for 1, immersed in a second layer of an impregnation liquid for 2, dried for 2, and sintered for 2 to obtain a bioceramic bone repair scaffold with a modified surface structure; Preferably, in step S2, the temperature of sintering 2 is 800-1000° C., and the time of sintering 2 is 30-180 min; Preferably, the time of the immersion 1 and the immersion 2 is independently selected from 5 to 30 minutes; Preferably, the temperatures of the drying 1 and the drying 2 are independently selected from 40 to 90° C., and the times of the drying 1 and the drying 2 are independently selected from 1 to 5 hours.

6. The preparation method according to claim 1, characterized in that: In the step S1, the ceramic powder is selected from at least one of β-tricalcium phosphate, α-tricalcium phosphate, whitworthia, hydroxyapatite, calcium silicate, magnesia chalcedony, and diopside; Preferably, the photosensitive resin is selected from at least one of the commercial photosensitive resin Ausbond A370 or Formlabs photosensitive resin; Preferably, the dispersant is selected from at least one of propylene glycol methyl ether, BYK-111, Triton X-100, KH-550, and KH-560.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the ceramic powder, the photosensitive resin and the dispersant is 1g: (0.3-0.5)g: (0.05-0.1)g; Preferably, the ball milling time is 28 to 56 hours.

8. The preparation method according to claim 1, characterized in that: The printing method is three-dimensional printing technology, and the molding accuracy of the three-dimensional printing technology is 30~100 μm, among which the pore size distribution of the bracket is 50~800 μm, accounting for more than 85%.

9. The preparation method according to claim 1, characterized in that: In the step S1, the debinding temperature is 400-700°C, and the debinding time is 180-300 min; Preferably, in the step S1, the temperature of the sintering 1 is 1150-1450° C., and the time of the sintering 1 is 120-500 min.

10. A bioceramic bone repair scaffold with modified surface structure prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing ZrO2 bone repair biological ceramic scaffold material through gradient dip-coating of HA

    CN107050513A

  • Controllable porous biological ceramic scaffold and preparation method and application thereof

    CN112479737A

  • 3D printing machinable biological ceramic scaffold as well as preparation method and application thereof

    CN112960988A

  • Surface modified composite porous scaffold material as well as preparation method and application thereof

    CN115887784A

  • The coated scaffold for regeneration of hard tissue with hydroxyapatite and / or collagen containing mesoporous bioactive glass and the method thereof

    KR1020120017225A